EMPATHY AND TOGETHERNESS IN THE ROISAN KONDANGAN TRADITION IN DEPOK, WEST JAVA - Syaiful, Syaiful Arifin; Fathi, Fathi Khairi Agani; Kholil Lur Rochman; Saifudin, Saifudin Amin (Jurnal Bimbingan Penyuluhan Islam, 2025)
This study aims to understand the meaning and role of the Roisan Kondangan tradition in strengthening social solidarity and preserving local wisdom values in the community of Depok, West Java. This tradition is a form of reciprocity in community events, involving contributions from residents as a manifestation of mutual aid and solidarity. This research is qualitative type. A qualitative approach was employed through direct observation, in-depth interviews, and documentation, with thematic analysis to uncover its social and symbolic meanings. Interviews were conducted with H. Muchtar, a Betawi traditional elder and Mrs. Jumiati, a PKK chairperson who doubles as an RT head in Limo, Depok. The research findings indicate that despite adjustments in the form of assistance, such as a shift from goods and cash to the use of digital technology, the Roisan Kondangan tradition remains relevant as a means of strengthening social bonds and fostering closer relationships among residents. The values of solidarity and empathy remain at the core of this practice, demonstrating adaptation to modern social dynamics without losing its collective essence. The main conclusion indicates that this tradition functions as a social medium that strengthens a sense of togetherness and collective awareness among the community, while also serving as an instrument for preserving local culture that remains relevant in the contemporary era. The implications of this research are significant in supporting efforts to preserve traditions and local wisdom as part of the cultural identity of the Depok community and Indonesian society in general.